Respuesta de las plantas de banano (musa aaa simmonds, cultivar williams) a las aspersiones foliares de diferentes fungicidas en el control de sigatoka negra (Mycosphaerella finjiensis Morelet). - Portilla Loor, Jairo Benjamín (2017)
Black Sigatoka caused by the fungus Mycosphaerella fijiensis, is considered to be the most important foliar disease affecting plantain and banana crops in the world, producing yield losses of up to 100%, when no measures are implemented for its management. The objective of the present investigation was to evaluate the response of banana plants (Musa AAA Simmonds, Williams cultivar) to the foliar sprays of four systemic fungicides Diethofencarb, Pyraclostrobin, Pyrimethanil and Epoxiconazole for the control of black sigatoka. The evaluation was carried out in the "La María" Experimental Farm belonging to the State Technical University of Quevedo, province of Los Ríos, with a duration of two months. A completely randomized design (DCA) and the Tukey test at 5% probability were used, five treatments and five observations were handled, having as treatments the following: T1 Diethofencarb 0.6 L ha-1, T2 (Pyraclostrobin 0.4 L ha -1), T3 (Pyrimethanil 0.5 L ha-1), T4 (Epoxiconazole 1.25 L ha-1) and T5 (Control). We handled 25 experimental units for an evaluation period (7, 14, 21, 28, 35, 42, 49 and 56) days after the application, the methodology used was Stover modified by Gaul. The results showed statistical differences in the efficacy variable when joining the averages of leaf two + leaf three, in residuality showed statistical differences of the treatments with respect to the control but not between treatments. Throughout the evaluation period, it was determined that Epoxiconazole obtained the best values in relation to the rest of the fungicides followed by Pyraclostrobin; However, in the leaf emission did not present statistical significance, the behavior of the witness was under the total infection of the fungus, concludes that the use of systemic fungicides is beneficial by increasing their control mechanisms against the disease.